Comparing traditional and automated conservation assessments for Himalayan species of Buddleja - Bishal Gurung; Gao Chen; Jia Ge (Oryx)
To compare the benefits and drawbacks of traditional and automated conservation assessments, we used a field-based study and automated conservation assessments using GeoCAT, red and ConR to assess four species of Buddleja (Scrophulariaceae), a cosmopolitan genus of flowering plants. Buddleja colvilei, Buddleja sessilifolia, Buddleja delavayi and Buddleja yunnanensis are endemic to the Himalayan region. They have not yet been assessed for the IUCN Red List of Threatened Species but are facing elevated risks of extinction because of various anthropogenic and environmental pressures. Buddleja sessilifolia and B. delavayi are listed as Plant Species with Extremely Small Populations in Yunnan, China, where they are known to be threatened. Although automated assessments evaluated B. delavayi and B. yunnanensis as Endangered and B. sessilifolia and B. colvilei as Vulnerable, our field studies indicated a different categorization for three of the species: B. delavayi and B. yunnanensis as Critically Endangered and B. sessilifolia as Endangered. Our findings indicate that the accuracy and reliability of assessment methods can differ and that field surveys remain important for conservation assessments. We recommend an integrated approach addressing these limitations, to safeguard the future of other species endemic to the Himalayan region.